Pengaruh Inflasi, Kurs, Dan Harga Minyak Bumi Dunia Terhadap Indeks Harga Saham Gabungan Di BEI Tahun 2010-2020 - Linda Listari; Febriyanto; Sri Retnaning Rahayu (Universitas Muhammadiyah Metro, 2025)
The development of the Composite Stock Price Index at the end of the year from 2010 to 2020 tends to fluctuate due to several factors. Factors that influence the Composite Stock Price Index are inflation, exchange rates and world oil prices. The objectives of this research are 1) To determine the effect of inflation on the Composite Stock Price Index on the BEI for 2010-2020. 2) To determine the effect of exchange rates on the Composite Stock Price Index on the IDX for 2010-2020. 3) To determine the influence of world oil prices on the Composite Stock Price Index on the BEI for 2010-2020. 4) To determine the joint influence of inflation, exchange rates and world oil prices on the Composite Stock Price Index on the BEI for 2010-2020. This research is a type of conclusive research that is quantitative in nature. The population in this study is monthly Composite Stock Price Index (IHSG) data recorded on the IDX from January-December 2010 to January-December 2020. The population in this study was 132 months, namely January-December 2010 to December 2020. The samples in this study numbered 11, namely from 2010 to 2020. The data obtained was analyzed using multiple linear regression equations, coefficient of determination, t test, and f test. Based on the results of the research and discussion, several conclusions can be drawn that 1) The inflation variable has no effect on the Composite Stock Price Index (IHSG). 2) There is a positive and significant influence between the exchange rate on the Composite Stock Price Index (IHSG). 3) The World Petroleum Price (ICP) variable has no effect on the Composite Stock Price Index (IHSG). 4) There is a positive and significant influence between inflation, exchange rates and World Petroleum Prices (ICP) simultaneously or together on the Composite Stock Price Index (IHSG)